213k views
17 votes
6 - 3 ²/⁵ =
What is 6 - 3 ²/⁵

User Arizafar
by
4.7k points

1 Answer

11 votes


~\hspace{7em}\textit{rational exponents} \\\\ a^{( n)/( m)} \implies \sqrt[ m]{a^ n} ~\hspace{10em} a^{-( n)/( m)} \implies \cfrac{1}{a^{( n)/( m)}} \implies \cfrac{1}{\sqrt[ m]{a^ n}} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ 6-3^{(2)/(5)}\implies 6-\sqrt[5]{3^2}\implies 6-\sqrt[5]{9}~~\approx ~~4.8

User IAhmed
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.